2018
DOI: 10.1001/jamapsychiatry.2018.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Middle School Interventions on Alcohol Misuse and Abuse in Mexican American High School Adolescents

Abstract: Study results support an association between a universal middle school intervention and alcohol misuse and alcohol use disorders among Mexican American high school students and implementation of universal middle school interventions to reach Latino communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…Given the costs stemming from high alcohol consumption, the workplace may be an appropriate setting for preventive strategies. However, previous studies often focused on young adults in school-based settings [ 13 , 14 ], and workplace-based prevention programs have solely been conducted outside of Sweden [ 5 , 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the costs stemming from high alcohol consumption, the workplace may be an appropriate setting for preventive strategies. However, previous studies often focused on young adults in school-based settings [ 13 , 14 ], and workplace-based prevention programs have solely been conducted outside of Sweden [ 5 , 15 - 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that the greatest promise for school SBIRT may be preventive‐providing students clear advice, accurate information and a respected adult who they can return to for questions or problems should they arise. The effectiveness of universal group‐based substance use prevention programs in schools has been demonstrated previously . A future study could examine the effectiveness of school‐based SBIRT as an intervention to prevent substance use, particularly among MS students.…”
Section: Discussionmentioning
confidence: 69%
“…Bridges/Puentes ( Gonzales et al, 2018 ) emphasizes risk reduction (prevention) as well as positive youth development (promotion) in multiple domains (family, school, and peers) ( Koning et al, 2013 ); Hodder et al (2017a) used a pragmatic intervention to implement available programs and resources targeting individual and environmental ‘resilience’ protective factors.…”
Section: Resultsmentioning
confidence: 99%
“…Diaz et al (2021) used the Primavera prevention program and showed that children from the control group were less likely to report current alcohol use at the end of the first year of the intervention. Gonzales et al (2018) used the Bridges/Puentes program, which significantly reduced the likelihood of developing an alcohol use disorder five years later. The results of Kulis et al (2020) ( Mantente REAL prevention program) showed relatively less frequent use of alcohol, and higher risk students reported relative reductions in the frequency of alcohol use, especially males.…”
Section: Resultsmentioning
confidence: 99%